(untitled) (Journal of the College of Education for Women, 2019)
Through the study of social work and social policy ( problems of marginalization and empowerment opportunities ) and taken a theoretically descriptive and analytical and highliyhed the role of social work in social policy its achieved only through community intraction and paamong all parties and according to social policies include of material resources and haman and integrated in to the planning and development framework with the aim of providing social services for allsegments of society and become the study in social work that include the introducation / and five chapters each chapter in cludes several detectives and each complements the other .1 – The absence of social development projects on social policy .2 – social policies contributed to the marginalization of the role of social .3 – neglected social policy of mang social problems .